Telomere repeat binding proteins are functional components of Arabidopsis telomeres and interact with telomerase - Schrumpfová, Petra Procházková; Vychodilová, Ivona; Dvořáčková, Martina; Majerská, Jana; Dokládal, Ladislav; Schořová, Sárka; Fajkus, Jiří (Plant journal, 2014)
Although telomere-binding proteins constitute an essential part of telomeres, in vivo data indicating the existence of a structure similar to mammalian shelterin complex in plants are limited. Partial characterization of a number of candidate proteins has not identified true components of plant shelterin or elucidated their functional mechanisms. Telomere repeat binding (TRB) proteins from Arabidopsis thaliana bind plant telomeric repeats through a Myb domain of the telobox type in vitro, and have been shown to interact with POT1b (Protection of telomeres 1). Here we demonstrate co-localization of TRB1 protein with telomeres in situ using fluorescence microscopy, as well as in vivo interaction using chromatin immunoprecipitation. Classification of the TRB1 protein as a component of plant telomeres is further confirmed by the observation of shortening of telomeres in knockout mutants of the trb1 gene. Moreover, TRB proteins physically interact with plant telomerase catalytic subunits. These findings integrate TRB proteins into the telomeric interactome of A. thaliana.
Keywords: telomerasa; Arabidopsis Proteins; Arabidopsis; proteiny huseníčku; telomery; Telomerase; proteiny vázající telomery; Telomere; Telomere-Binding Proteins